Early childhood experiences in language arts : emerging literacy - Machado, Jeanne M. (Albany, N.Y. : Delmar, 1999)
Language development-emerging literacy in the young child. Developing language arts programs. Listening-literate beginnings. Introducing literature. Speech growth-conversation, expression, and dramatization. Writing - print awareness and use. Reading-a language art. Settings promoting literacy-at home and school.
Keywords: Literacy; Language arts; Language acquisition; Literacy; Language arts (Early childhood); Language acquisition -- Parent participation